Construction and building materials (2012)
This study researches into solid waste management in South-West Nigeria in relation to pollution control using a an North as a case study. The generation pattern storage, collection and transportation, and the final disposal of solid waste ocean government are all discussed. Data used for this study were collected by the use of structured questionnaires and oral interviews. Analysis of the data revealed that all the functional elements of solid waste management system in the local government and the city of lbadan in general as practiced by existing institution - Ibadan Solid Waste Management Authority, are engulfed with fundamental problems which apparently have been the reason why institutions are unsuccessful in the efficient management of solid waste and control of environmental pollution. The various problems are identified, analyzed and discussed, pragmatic means of solving the problems, such as the encouragement of waste recycling; the active provision